The Impact of Financial Ratios on Company Value - Wahyuni, Dhian; Nazar, Rafki; Gumilar, Aleta Sophiana Putri (UNIVERSITAS PAKUAN, 2023)
Company value is the perception of investors on the achievement of a company based on an increase in stock price. Increasing stock prices impact company value, attracting investors to invest in the company. This study investigates the condition of financial ratios such as profitability, liquidity, company age, and dividend policy and their effect on company value. The sample used in this study is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. This study used purposive sampling and produced observational data from 280 companies. Using panel data regression analysis, the results show that profitability, liquidity, company age, and dividend policy simultaneously affect company value. While partially, profitability has a positive effect on the company's value. While liquidity, company age, and dividend policy do not affect company value. This research provides empirical evidence on research topics related to internal company factors that affect company value